Impact of Biogenic Amines on the Growth of Green Microalgae - Oleskin, Alexander V.; Postnov, Andrey L.; Boyang, Cao (Journal of Pharmacy and Nutrition Sciences, 2021)
Background: The goal of this research project was to test various neuroactive amines in the capacity of growth stimulators/accelerators of the green microalgae Scenedesmus quadricauda and Chlorella vulgaris that have much biotechnological potential because they can be used for producing drugs, food ingredients, cosmetics, and biofuel. The issue of the ecological role of the biogenic amines in terms of interspecies communication in aqueous ecosystems was also addressed in this work. Methods: S. quadricauda strain GEHD and C. vulgaris strain ALP were cultivated in the light with constant aeration at 24oC in a minerals-containing medium. Experimental systems contained 1, 10 or 100 mM of dopamine hydrochloride, histamine hydrochloride, norepinephrine hydrochloride, or serotonin hydrochloride that were added at inoculation as freshly prepared aqueous solutions. Algal cells were counted using a light microscope , and their number in 1 mL of culture was calculated. The culture liquid and sonicated biomass of S. quadricauda and C. vulgaris were tested for the presence of endogenous amines using high-performance liquid chromatography (HPLC) with an amperometric detector. Results: The biogenic amines serotonin, norepinephrine, dopamine, and histamine significantly stimulated the growth of S. quadricauda, at concentrations of 1 and/or 10 mM but not 100 mM. Histamine was the most efficient stimulator, causing an average 65% increase in biomass accumulation at the end of the cultivation period. The effects of serotonin, dopamine and histamine on C. vulgaris were reported in our previous publication [1], but this work contains the results of our experiments with the previously untested norepinephrine that slightly stimulated the growth of C. vulgaris. HPLC analysis failed to reveal any endogenous amines in the culture liquid and biomass of both microalgae. Conclusions: Since biogenic amines stimulate the growth of the microalgae S. quadricauda and C. vulgaris but are not synthesized by them, we suggest that the algae normally respond to amines produced by other components of aqueous ecosystems, including zooplankton and fish that are known to release significant amounts of biogenic amines into the environment. The data obtained hold some promise with regard to developing a relatively economical technique of boosting algal biomass production.